Letter to Editor Concerning the Article: The Effect of Oral Psyllium Herbal Laxative Powder in Prevention of Hemorrhoids and Anal Fissure During Pregnancy - Masood Sepehrimanesh (Shiraz University of Medical Sciences, 2016)
Introduction Pneumatosis intestinalis (PI) is a broad term that describes the presence of gas in the bowel walls. The colon is affected in 36% of cases. Eosinophilic colitis (EC) is a rare form of colitis that is characterized mainly by eosinophilia in blood and affected tissues. Although eosinophilic colitis responds well to conservative treatment, yet the association of PI could be an indication of emergent surgery. Case Presentation A 48-year-old female patient with a history of recurrent attacks of abdominal pain and distention that did not respond to conservative treatment, was hospitalized and investigated thoroughly. The result of abdominal computed tomography (CT) scan indicated the presence of pneumatosis coli. Based on the findings of the CT scan, colonoscopy was done revealing hyperemic and hypertrophied mucosa at the hepatic flexure, from which multiple punch biopsies were taken for histopathological assessment. The pathological examination of these biopsies detected a diffuse active colitis of moderate severity with excess eosinophils (10 - 15/HPF), which is consistent with the diagnosis of EC. The patient improved dramatically on fluid therapy and antibiotics with complete resolution of pneumatosis coli in the follow up CT scan. However, the patient developed a severe relapse of symptoms once oral intake was resumed and this time the conservative treatment failed to improve the condition. Surgery was indicated and laparoscopic right hemicolectomy with primary anastomosis and covering ileostomy was done. The patient was free of symptoms after the operation and her postoperative course was uneventful with no complications encountered. Conclusions Eosinophilic colitis usually has a good prognosis, however its association with pneumatosis coli could reflect a serious damage to the colonic mucosa. Although eosinophilic colitis responds well to medical treatment, yet in certain cases where clinical signs are evident and pneumatosis coli is present, surgical intervention is the treatment of choice.